Cytotoxicity evaluation of dental and orthodontic light‐cured composite resins - Raoul Bationo; Ablassé Rouamba; Abdoulaziz Diarra; Monique Lydie Ahia Beugré‐Kouassi; Jean‐Bertin Beugré; Fabienne Jordana (Wiley, 2021)
Abstract Introduction The aim of this study was to determine the cytotoxicity of light‐cured composite resins (Clearfil ES‐2, Clearfil ES Flow, Filtek Supreme XTE, Grengloo, Blugloo, Transbond XT, and Transbond LR) then to assess leachable components in contact with human gingival fibroblasts (GFs) and to quantity detected bisphenol A (BPA). Methods Light‐cured composite resin discs were immersed for 24 hours in gingival fibroblastic medium (n = 3 for each product) and in control medium (n = 2 for each product) contained in plate. Cytotoxicity of the products (n = 95) was determined by the measure of cell viability using MTT assay after reading the optical densities of the plates. The analysis of leachable components was done by gas phase chromatography and mass spectrometry (GC-MS) and detected BPA was quantified. The limit of quantification was 0.01 μg/mL. Statistical analyses were performed by using IBM SPSS Statistics 20 and Kruskal-Wallis and Mann-Whitney U‐tests were applied. Results Cell viabilities were between 85 and 90%. Many chemical compounds including triethylene glycol dimethacrylate (TEGDMA) and BPA were identified. The average concentrations were 0.67 μg/mL ± 0.84 in the control medium and 0.73 μg/mL ± 1.05 in the fibroblastic medium. Filtek Supreme XTE presented the highest concentration of BPA with 2.16 μg/mL ± 0.65 and Clearfil ES Flow presented the lowest with 0.25 μg/mL ± 0.35. No BPA was detected with Transbond XT and Transbond LR. Clearfil ES Flow, Filtek Supreme XTE, Grengloo and Transbond LR presented residual TEGDMA. Conclusions Light‐cured composite resins are slightly cytotoxic opposite GFs and release many components including BPA and TEGDMA. Clinical precautions should be taken to decrease the release of these monomers.